Molecular interactions mediating T cell antigen recognition. - Van Der Merwe, P; Davis, S (2003)
Over the past decade, key protein interactions contributing to T cell antigen recognition have been characterized in molecular detail. These have included interactions involving the T cell antigen receptor (TCR) itself, its coreceptors CD4 and CD8, the accessory molecule CD2, and the costimulatory receptors CD28 and CTLA-4. A clear view is emerging of how these molecules interact with their ligands at the cell-cell interface. Structural and binding studies have confirmed that the proteins span small but comparable distances and that, overall, they interact very weakly. However, there have been important surprises as well: that TCR interactions with peptide-MHC are topologically constrained and characterized by considerable conformational flexibility at the binding interface; that coreceptors engage peptide-MHC with extraordinarily fast kinetics and at angles apparently precluding direct interactions with the TCR bound to the same peptide-MHC; that the structural mechanisms allowing recognition by costimulatory and accessory molecules to be weak and yet specific are very heterogeneous; and that because of differences in both binding affinity and stoichiometry, there is enormous variation in the stability of the various costimulatory receptor/ligand complexes. These studies provide the necessary framework for exploring how these molecular interactions initiate T cell activation.